Comparison of Gabapentin and Placebo as Pre-emptive Analgesic Agent for Postoperative Analgesia in Patients Undergoing Elective Abdominal Hysterectomy under Spinal Anaesthesia: A Randomised Controlled Trial - Divyang Satishkumar Sutaria; Anjali Tripathi; Vishwa Rameshbhai Patel; Chandrika V Bhut (Journal of Clinical and Diagnostic Research)
Introduction: Pre-emptive analgesia is a form of pain management that seeks to prevent alterations in the way the body processes incoming pain signals. Gabapentin is a compound that exhibits structural similarities to gamma-aminobutyric acid. It has been found to possess powerful pain-relieving properties and can also help prevent seizures. Additionally, it is purported to have greater efficacy in reducing the neuropathic component of acute nociceptive pain following surgical procedures. Aim: The purpose of the study was to assess the efficacy of gabapentin and placebo in providing pre-emptive analgesia for postoperative pain management among patients undergoing elective abdominal hysterectomy under spinal anesthesia. Materials and Methods: A single-blind randomised controlled trial was conducted among patients undergoing elective abdominal hysterectomy who had American Society of Anesthesiologists (ASA) physical status I-II. Sixty-eight participants, aged between 35 and 70 years, were randomised into two groups: group G (n=34) was administered 600 mg of gabapentin in tablet form, whereas group P (n=34) received a placebo, two hours prior to the surgery. Participants were assessed for vital signs and pain using the Visual Analogue Score (VAS), while the level of sedation was determined using the Ramsay Sedation Score (RSS). An injection of Diclofenac 75 mg intravenously was administered as an analgesic on an as-needed basis. The requirement for analgesia was monitored over the next 24 hours. Statistical analysis was performed using the independent Student’s t-test, Mann-Whitney U Test, and Chi-square test. Results: Both groups were comparable with respect to demographic profile (age, ASA physical status) and haemodynamic variables {pulse rate, Mean Arterial Pressure (MAP), Peripheral Oxygen Saturation (SpO2)}, with a p-value>0.05. The mean duration of the first rescue analgesic requirement for group G (12.82±4.50 hours) was significantly higher than for group P (8.58±2.54 hours), with a p-value of 0.002. The mean duration of the second and third rescue analgesic requirement for group G was 13.50±2.97 hours and 21±3.00 hours, respectively, while for group P it was 15.78±3.20 hours and 22±2.08 hours, respectively. Therefore, group G experienced a significantly longer duration of analgesia, as evidenced by the mean duration of the first rescue analgesic requirement. No significant side effects were observed in either group. Conclusion: Gabapentin 600 mg when used as a pre-emptive analgesic provides analgesic effects and reduces the requirement for rescue analgesia while maintaining stable haemodynamics perioperatively. Therefore, it serves the purpose of multimodal analgesia for improved anaesthetic management.